2008
DOI: 10.4184/asj.2008.2.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Long Level (T4-L1) Spinal Epidural Abscess in a Diabetic Patient - A Case Report -

Abstract: Spinal epidural abscesses are uncommon, but potentially devastating and often fatal. They can be found in normal patients, but they are more prevalent in immunocompromised patients, such as intravenous drug users, diabetics, chronic renal failure patients, pregnant women, and others. Timely diagnosis and treatment are the keys to optimizing outcome. Traditionally, treatment has comprised parenteral antibiotics and possible surgical intervention, such as decompression by pus drainage. We treated a long level (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 6 , 7 SEA lesions are more common in the thoracic and lumbar segments. 8 Men aged older than 60 years are more likely to have SEA, with a male to female ratio of 3:1. 9 , 10 SEA is divided into (1) the acute type in which all lesions are pus, (2) the subacute type with coexistence of pus and granulation tissue, and (3) the chronic type with mainly granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 SEA lesions are more common in the thoracic and lumbar segments. 8 Men aged older than 60 years are more likely to have SEA, with a male to female ratio of 3:1. 9 , 10 SEA is divided into (1) the acute type in which all lesions are pus, (2) the subacute type with coexistence of pus and granulation tissue, and (3) the chronic type with mainly granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the abscess also plays a crucial role in treatment considerations. Spinal epidural abscesses most frequently occur at the lumbar level (48%), followed by the thoracic (31%) and cervical (21%) levels [ 3 ]. The development of SEA can be attributed to hematogenous spreading, direct spread from adjacent structures, or direct inoculation from invasive procedures [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adogwa et al in their study of 82 patients with spinal epidural abscess found that 70% were ventrally located and 30% dorsally located9. Hwang et al reported a case of long level ventrally located thoracic spinal epidural abscess, where multilevel laminectomy failed to achieve motor recovery 14) . Hence ventrally located abscesses are difficult to drain using standard techniques.…”
Section: Discussionmentioning
confidence: 99%